METODE GURU DALAM MEMOTIVASI MEMBACA PESERTA DIDIK KELAS 3 SDN 53 KOTA BIMA TAHUN PELAJARAN 2022/2023 - Nurlaila Nurlaila; Marsina Marsina; Syarini Syarini; Adiansyah Adiansyah (Prodi PAI STIT Sunan Giri Bima, 2022)
The lack of reading motivation that occurs in students is a problem that must be taken seriously in education. Remembering that success in educating is when you have been able to change the personality of students in an understanding from those who can't to can. The focus of our research is to look at teacher methods in motivating and at the same time overcoming the lack of reading power in students at SDN 53 Kota Bima. The method we use in this research is descriptive qualitative method. The results of this study found that the reading power of students at SDN53 Kota Bima, more specifically grade 3, was still very low, although most of them were already able to read, but there was no habit of reading yet. Teachers communicate with parents to always monitor what their children are doing, provide time limits for using cellphones and make a special schedule for when to study and when to hold cellphones. The methods, methods and facilities provided are also used by educators who are very good, such as giving students freedom to choose, even with certain limitations and always watching over them.